2022
DOI: 10.1136/lupus-2021-000599
|View full text |Cite
|
Sign up to set email alerts
|

Association between systemic lupus erythematosus and disruption of gut microbiota: a meta-analysis

Abstract: ObjectiveRecent studies reported that SLE is characterised by altered interactions between the microbiome and immune system. We performed a meta-analysis of publications on this topic.MethodsCase–control studies that compared patients with SLE and healthy controls (HCs) and determined the diversity of the gut microbiota and the abundance of different microbes were examined. Stata/MP V.16 was used for the meta-analysis. A Bonferroni correction for multiple tests was used to reduce the likelihood of false-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Genetic factors, such as histocompatibility complex (MHC) polymorphism, and environmental factors, including ethnicity, diet and geography, have been correlated to the gut microbiota structure ( 19 21 ). A meta-analysis of studies comparing the fecal microbiome of SLE patients and healthy controls showed a lower diversity in SLE patients with a lower abundance of Ruminococcaceae ( 9 ). SLE patients with active lupus disease showed less diverse gut microbiota but a significantly higher abundance of the bacterial phylum Proteobacteria ( 22 ).…”
Section: Evidence Of Gut Dysbiosis and Leaky Gut In Slementioning
confidence: 99%
See 2 more Smart Citations
“…Genetic factors, such as histocompatibility complex (MHC) polymorphism, and environmental factors, including ethnicity, diet and geography, have been correlated to the gut microbiota structure ( 19 21 ). A meta-analysis of studies comparing the fecal microbiome of SLE patients and healthy controls showed a lower diversity in SLE patients with a lower abundance of Ruminococcaceae ( 9 ). SLE patients with active lupus disease showed less diverse gut microbiota but a significantly higher abundance of the bacterial phylum Proteobacteria ( 22 ).…”
Section: Evidence Of Gut Dysbiosis and Leaky Gut In Slementioning
confidence: 99%
“…NSAIDs can induce mitochondrial and endoplasmic reticulum damage and oxidative stress in intestinal epithelial cells, enhancing gut permeability and local inflammation ( 110 ). Treatment of SLE patients with hydroxychloroquine reduced the abundance of Enterobacteriaceae , and glucocorticoids, a group of drugs broadly used to treat lupus, reduced microbial diversity ( 9 ). The calcineurin inhibitor tacrolimus (FK 506) increased gut permeability in humans and rats through inhibiting mitochondrial respiration in gut epithelial cells ( 111 ).…”
Section: Mechanisms Leading To the Loss Of Barrier Integrity In Lupusmentioning
confidence: 99%
See 1 more Smart Citation
“…Their decrease may lead to leaky gut. Recently, a meta-analysis of relevant research publications from around the world has shown a decreased abundance of Ruminococcaceae with SLE, especially in Chinese patients ( 48 ). Overall, our results show that a specific microbial signature in patients with SLE with more severe dysbiosis was found and correlated strongly with the SLEDAI activity score, suggesting the contribution of gut microbiota to the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits the growth of intestinal bacterial strains in a dose-dependent manner, which results in reduced stimulation of immune system activation and decreased tolerance to Treg cell induction [ 101 ]. In addition, the use of hydroxychloroquine in SLE appears to reduce the abundance of Enterobacteriaceae [ 102 ]. Concerning other standard treatment options, no significant data have emerged to date.…”
Section: Potential Strategies Of Gut Microbiota Modulationmentioning
confidence: 99%